Pain Experience and Pain Control among Trauma Patients in Oral and Maxillofacial Surgery Clinic of Mulago Hospital, UgandaPain Experience and Pain Control among Trauma Patients in Oral and Maxillofacial Surgery Clinic of Mulago Hospital, Uganda - Kugonza, Gonzaga; Kasangaki, Arabat; Muwazi, Louis; Rwenyonyi, Charles Mugisha (International Journal of Research Studies in Medical and Health Sciences, 2018)
Pain is an unpleasant sensory and emotional experience often described as tissue damage, in the presence/absence of actual tissue damage or somatic disease. The aim of the present study was to establish pain experience of trauma patients and pain management practices of health care practitioners during invasive interventions in the Oral and Maxillofacial Surgery Clinic of Mulago Hospital. This was a cross sectional study on 187 trauma patients scheduled for invasive interventions who were consecutively recruited. Pain experience was evaluated using a horizontal Visual Analogue Scale to ascertain their pain experience before and during invasive procedures. During surgical invasive procedure, no and mild pain were defined as successful whereas moderate and severe pain were considered failed pain control.Before invasive intervention, 74.3% of the participants reportedly experienced either no or mild pain. During invasive procedures, all participants reported feeling some degree of pain; 21.4% being mild in nature. Overall, there was no consistency in pain control techniques applied for any given intervention with the exception of surgical toilet and zygomatic arch elevation, where anesthetic infiltration was the only technique applied. During surgical toilet, pain control was successful in 84.6% of the participants, while splinting of teeth and intermaxillary fixation, infiltration was successful in 50% and <20% of the participants, respectively. Eyelet wire removal was performed in 40.1% (n=75) of the participants with no form of pain control with 70.6% (n=53) of the participants reporting severe pain during the procedure.Most participants reported a higher degree of pain during the intervention compared to their pre-intervention time. No pain control was provided to patients during eyelet wire removal, most of whom reported severe pain. Most interventions had varied approaches to the pain control techniques with the exception of surgical toilet and elevation of the zygomatic arch.
Keywords: local anaesthesia, lignocaine, pain control, pain experience, trauma, visual analogue scale